Yoga: A Spiritual Science for Holistic Well-being - Dr. Renjith P.G (Revista Electronica de Veterinaria, 2023)
Yoga Darsana, one of the six classical systems of Indian philosophy, offers a comprehensive framework for understanding human consciousness and the nature of reality. Rooted in the ancient texts of the Yoga Sutras by Patanjali, Yoga Darsana emphasizes the union of the individual self with the universal consciousness (Brahman) through disciplined practice. This abstract explores the scientific dimensions of Yoga, particularly how its concepts align with and inform modern scientific understandings of psychology, neuroscience, and health.